2012
DOI: 10.23960/j.hptt.212185-191
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis Penyakit Mosaik (Soybean Mosaic Virus) Terbawa Benih Kedelai

Abstract: Soybean mosaic disease is wide spread throughout soybean-growing countries. Incidence of this disease in East Java is caused by Soybean mosaic virus (SMV) and cowpea mild mottle virus (CMMV).  This aim of study was to find the etiology of  disease at 14-28 days after planting (dap) on soybean.  Research was done by observing visual symptoms. Visual symptoms confirmed by infectivity test, serology assay,electron microscopy (EM) and molecular detection. Results from experiment indicated that soybean plants (14-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Rendahnya produktivitas kedelai karena serangan hama dan penyakit, untuk serangan penyakti salah satunya disebabkan oleh serangan cendawan Phakopsora pachyrizi (penyebab penyakit karat daun) terutama saat musim kemarau (Sumartini, 2016). Hal ini sejalan dengan pernyataan dari (Adisarwanto, 2008), yang menyatakan bahwa karat daun dapat menurunkan jumlah polong yang dihasilkan dengan kisaran 30% sampai dengan 60%. Hal tersebut disebabkan karena daun kedelai yang terserang cendawan Phakopsora pachyrizi mengalami penguningan, sehingga daun tersebut mudah gugur sebelum terjadi pengisian polong.…”
Section: Pendahuluanunclassified
“…Rendahnya produktivitas kedelai karena serangan hama dan penyakit, untuk serangan penyakti salah satunya disebabkan oleh serangan cendawan Phakopsora pachyrizi (penyebab penyakit karat daun) terutama saat musim kemarau (Sumartini, 2016). Hal ini sejalan dengan pernyataan dari (Adisarwanto, 2008), yang menyatakan bahwa karat daun dapat menurunkan jumlah polong yang dihasilkan dengan kisaran 30% sampai dengan 60%. Hal tersebut disebabkan karena daun kedelai yang terserang cendawan Phakopsora pachyrizi mengalami penguningan, sehingga daun tersebut mudah gugur sebelum terjadi pengisian polong.…”
Section: Pendahuluanunclassified
“…Virus infection on soybeans have the potential to cause yield loss and reduce the quality of seeds. Soybean mosaic virus (SMV) (Andayanie 2012), Cucumber mosaic virus strain soybean (CMV-S) and Pepper yellow leaf curl virus (PYLCV) (Rahim et al 2015) were reported recently infecting soybean plants in Java. Cowpea mild mottle virus (CPMMV) was first reported to cause systemic mottling, chlorotic blotches and leaf malformations in cowpea (Vigna unguiculata L.) in 1973 and to be widespread in the Eastern Region of Ghana, West Africa.…”
Section: Introductionmentioning
confidence: 99%